Palaeohydrogeology and Transport Parameters Derived from 4He and Cl Profiles in Aquitard Pore Waters in a Large Multilayer Aquifer System, Central Australia. (20th November 2017) - Priestley, Stacey C.; Kleinig, Tavis; Love, Andrew J.; Post, Vincent E. A.; Shand, Paul; Stute, Martin; Wallis, Ilka; Wohling, Daniel L.
Abstract : A study of chloride and 4 He profiles through an aquitard that separates the Great Artesian Basin from the underlying Arckaringa Basin in central Australia is presented. The aquitard separates two aquifers with long water residence times, due to low recharge rates in the arid climate. One-dimensional solute transport models were used to determine the advective flux of groundwater across the aquitard as well as establish any major changes in past hydrological conditions recorded by variations of the pore water composition. This in situ study showed that both diffusion and slow downward advection (v z = 0.7  mm/yr) control solute transport. Numerical simulations show that an increase in chloride concentration in the upper part of the profile is due to a reduction in recharge in the upper aquifer for at least 3000 years. Groundwater extraction since 2008 has likely increased chloride and 4 He concentrations in the lower aquifer by pulling up water from deeper layers; however, there has been insufficient time for upward solute transport into the pore water profile by diffusion against downward advection. The transport model of 4 He and chloride provides insight into how the two aquifers interact through the aquitard and how climate change is being recorded in the aquitard profile.